Improving the Symbolic Thinking Ability of Children Aged 4-5 Years through Flashcard Media - Mayang Sari, Novia Putri; Sari, Nisa Kurnia; Alfiatun, Alfiatun; Sulistiani, Nur; Kinasih, Kinasih; Widati, Sri; Fitriyah, Qonitah Faizatul (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2024)
This research aimed to improve cognitive development in children aged 4-5 years in general and specifically to improve the symbolic thinking abilities of children aged 4-5 years through flashcard media. The samples that researchers observed in this research were children in group A of TK Aisyiyah Mutiara Hati Surakarta and TK Aisiyah III Surakarta.The samples of this research comprised 26 children consisting of 13 boys and 13 girls. This research was classroom action research using the Kemmis and Mc. Taggart’s model consists of 4 stages: planning, action, observation, and reflection. This research used data collection techniques through observation and documentation. The data analysis techniques applied descriptive analytics. The research results showed an increase in the ability to think symbolically by using flashcard media for two cycles, which fell into the Very Well Developed (Berkembang Sangat Baik/BSB) category. Thus, it can be concluded that the use of learning media in the form of flashcard media could improve symbolic thinking abilities in children aged 4-5 years.